Correlation analysis between clinical characteristics of adult patients with Mycoplasma pneumoniae pneumonia and 23S rRNA A2063 gene in alveolar lavage fluid - Yuexun Huang; Haolin Wen; Ying Liu; Haomin Xie; Linwei Wu; Zhenyang Fu; Chen Sicheng; Dacheng Zhang (BMC Pulmonary Medicine)
Abstract Background To investigate the clinical features and laboratory and imaging characteristics of patients with mutations in the 23S rRNA A2063G drug resistance gene in the alveolar lavage fluid of adults with MPP. Methods Sixty-one cases of adult MPP were retrospectively analyzed. Based on the detection of the 23S rRNA A2063G resistance gene, the patients were classified into drug resistance gene-positivity (resistance group) and drug resistance gene-negative (sensitivity group) groups. The patients' general information, clinical manifestations, and relevant laboratory and chest High-Resolution Computed Tomography (chest HRCT) data were collected. The data were analyzed by t tests, rank-sum tests, chi-square tests, multifactor logistic regression analyses and other statistical methods. Results Among 61 patients, 44 (72.1%) were in the resistance group, and 17 (27.9%) were in the sensitivity group. The fever rate, duration of fever and incidence of extrapulmonary complications were significantly greater in the resistance group than in the sensitivity group (P < 0.05). Fibrinogen content was significantly higher in the resistant group than in the sensitivity group (P < 0.05). Forty-two patients (95.5%) in the resistance group had imaging manifestations of centrilobular distribution, tree-in-bud sign, ground-glass opacity, and thickening of the bronchial wall, which were significantly greater than those in the sensitivity group. The difference was statistically significant (P < 0.05). Logistic regression analysis demonstrated that these imaging manifestations had a significant positive effect on the drug resistance gene-positive group. Conclusion Adults with MPP with 23S rRNA A2063G drug resistance gene mutation have more severe clinical presentations, higher serum fibrinogen levels and a greater incidence of extrapulmonary complications. Serum fibrinogen levels and imaging signs of infectious bronchiolitis are informative for the early identification of drug-resistant Mycoplasma pneumoniae in adults.